UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENGENAL MALAIKAT DAN TUGAS-TUGASNYA MELALUI METODE MAKE A MATCH DI SD NEGERI SENDANG 01 KECAMATAN BRINGIN KABUPATEN SEMARANG TAHUN PELAJARAN 2017/2018 - Sri Sulastri (JANACITTA, 2020)
This study uses a qualitative approach with the type of Classroom Action Research (PTK). The research subjects were fourth grade students of Sendang 01 elementary school, Bringin District, Semarang Regency. The data collection techniques used in this study were (1) participant observation method (2) the test method The data in this study are divided into two types, namely quantitative data and qualitative data. The research was carried out in three stages. The first stage is a pre-cycle with the lecture method with an average score of 59.55 of the Minimum Completion Criteria (KKM) of 70 with 27.27% student completeness. The second stage of cycle 1 results from the class average score of 69.55 which was achieved by 13 students who completed out of 22 students. With completeness reaching 59.09%. The third stage of the second cycle with an average grade score of 81.82 which was achieved by 21 students who completed out of 22 students with completeness reaching 95.45%. Based on these data, with the application of the Make a Match method, cycles I and II, it can be seen that there is an increase in learning outcomes after the application of the Make a Match method.